PENGARUH PENYERTAAN MODAL DESA DAN SISA HASIL USAHA BUMDES BERSAMA “BANGKIT MANDIRI” TERHADAP PENDAPATAN ASLI DESA DI KECAMATAN NITA - Nuwa, Cicilia Ayu Wulanari; Apelabi, Kristianus Bai (AKSIOMA : Jurnal Manajemen, 2022)
Abstract This research belongs to the type of causality research, namely research that wants to find a causal relationship between the variables of Village Equity Participation and Remaining Profits from BUMDes Joint "Bangkit Mandiri" to Village Original Income in Nita District. This research also includes a type of quantitative research in which the researcher first develops a hypothesis. The next step is tested quantitatively until finally arriving at the final findings in a tested hypothesis. The results of the F statistical test show that together with the two (2) independent variables, namely Village Capital Inclusion (X1) and BUMDes Business Results (X2), have no significant effect on Village Original Income (Y). The results of the t-statistical test show that individually (partial), the Village Capital Participation Variable (X1) has no significant effect on the Village Original Income Variable (Y). This means that if the Equity Participation variable (X1) increases, the increase in the Equity Participation variable does not increase the Village Original Income (Y) variable. Meanwhile, the residual income variable for BUMDes (X1) has no significant effect on the Village Original Income Variable (Y). This means that if the BUMDes residual income variable (X2) increases, the increase in the BUMDes remaining operating income variable does not increase the village original income variable (Y). Furthermore, the contribution of the two independent variables in this study which consists of Village Capital Inclusion (X1) and Rest of BUMDes Business Results (X2), can explain the variation of ups and downs in Village Original Income (Y) in all villages in Nita District by 1.3%. At the same time, the remaining 98.7% is explained by other variables that are not included in this research model.